2021
DOI: 10.3389/fgene.2021.630310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in TNFSF4 and TNFSF8 Are Associated With the Risk of HCV Infection Among Chinese High-Risk Population

Abstract: BackgroundThe tumor necrosis factor superfamily (TNFSF) and TNF receptor superfamily (TNFRSF) play important roles in the immune responses to infections. The aim of this study was to determine the impact of single nucleotide polymorphisms (SNPs) of several TNFSF/TNFRSF genes on the risk of hepatitis C virus (HCV) infection in the Chinese high-risk population.MethodsThe TNFSF4-rs1234313, TNFSF4-rs7514229, TNFSF8-rs3181366, TNFSF8-rs2295800, TNFRSF8-rs2298209, and TNFRSF8-rs2230625 SNPs were genotyped in 2309 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Similarly, neutrophils may also mediate tissue damage in trachomatous scarring, potentially through the production of reactive oxygen species and matrix metalloproteinases ( Barton et al., 2023 ). Some of the identified viral genes are also involved in other viral diseases, such as IKZF3 which promotes proliferation of HIV-1-infected cells ( Wei et al., 2023 ), IRF8 which is involved in the induction of downstream antiviral genes in monocytes by DNA viruses (such as HSV-1) but not RNA viruses ( Luo et al., 2022 ), and variants in TNFSF4 which are associated with the risk of HCV infection ( Fu et al., 2021 ). Thus, our results on human corneal tissue identify several mechanisms that are involved in the pathogenesis of viral infection and provide the foundation for a potential translation of previous findings from animal models to humans as novel therapeutic strategies for viral keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, neutrophils may also mediate tissue damage in trachomatous scarring, potentially through the production of reactive oxygen species and matrix metalloproteinases ( Barton et al., 2023 ). Some of the identified viral genes are also involved in other viral diseases, such as IKZF3 which promotes proliferation of HIV-1-infected cells ( Wei et al., 2023 ), IRF8 which is involved in the induction of downstream antiviral genes in monocytes by DNA viruses (such as HSV-1) but not RNA viruses ( Luo et al., 2022 ), and variants in TNFSF4 which are associated with the risk of HCV infection ( Fu et al., 2021 ). Thus, our results on human corneal tissue identify several mechanisms that are involved in the pathogenesis of viral infection and provide the foundation for a potential translation of previous findings from animal models to humans as novel therapeutic strategies for viral keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…TNFSF8 was highly expressed in PH037 alone and was also enriched in CD4 + Naïve T-cells and CD4 + Treg cells ( Figures 2L, M ). Furthermore, previous research have found that TNFSF8 was associated with regulation of immune response ( 30 ) and high risk of hepatitis infection ( 31 ). In general, our research found that abnormal distribution and proportion of T-cells can be a characteristic of HS; these T-cell enriched functions and genes have certain characteristics, which are mainly manifested through immunosuppression.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the possible influence of genetic background on SFTSV susceptibility, clinical manifestations, and outcomes was difficult to exclude, despite the underlying interpersonal transmission through contact with blood among family members. Moreover, the infections of a variety of viruses, such as hantavirus, dengue virus, influenza virus, and hepatitis C virus, had also been verified to correlate with genetic factors ( Xu-Yang et al., 2016 ; Kenney et al., 2017 ; Di Pucchio and Sekaly, 2020 ; Li Y. et al., 2020 ; Fu et al., 2021 ).…”
Section: Host Genetic Factorsmentioning
confidence: 99%